Social Media Marketing in Tourism and Hospitality - Minazzi, Roberta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book describes ongoing developments in social media within the tourism and hospitality sector, highlighting impacts on both the demand and the supply side. It offers a combination of theory and practice, with discussion of real-life business experiences. The book is divided into three parts, the first of which provides an overview of recent trends in social media and user-generated content, clarifies concepts that are often used in an overlapping way and examines the (3z(Bdigitization of word of mouth(3y (Bvia online networks. The second part analyzes the impacts that social media can have on traveler behavior for each step in the travel process and also on suppliers, highlighting opportunities, threats and strategies. In the third part of the book, future potential trends deriving from the mobile marketing technologies are explored and possible methods for social monitoring by means of key performance indicators are examined. It is considered how engaging customers and prospects by means of social media might increase customer loyalty, foster electronic word-of-mouth communication, and consequently have important effects on corporate sales and revenues. The discussion encompasses methods to measure company performance on each of the social media in order to understand the optimal mix that will support and improve business strategies.s
Keywords: Economics; Information systems; Marketing; Mass media; Economics/Management Science; Tourism Management; Media Management; Marketing; Innovation/Technology Management; Media Research; Information Systems and Communication Service